A Danish population‐based cohort study of desmopressin use in adults with nocturia or nocturnal enuresis. Issue 2 (11th July 2018) - Juul, Kristian Vinter; Schrøder, Marie Krarup; Mahler, Birgitte; Rittig, Søren; Nørgaard, Jens Peter
Abstract : Objective: This study investigated how desmopressin is prescribed to adults in Denmark. Methods: All adult users of desmopressin over an 8‐year period were identified from the Danish National Prescription Registry. Adult patients with nocturia or nocturnal enuresis (NE) were identified by indication codes for "frequent nocturnal voiding" or "involuntary nocturnal voiding", respectively. Patient demographics, desmopressin formulation and dose, and concomitant medication were investigated. Results: In all, 13 871 adults with nocturia and 2872 adults with chronic (i.e. >10 prescriptions) NE were given 102 547 and 43 712 desmopressin prescriptions, respectively. Across the entire patient cohort, 57% were women and mean patient age was 62 years. Over 40% of prescriptions were to elderly patients (≥65 years), and desmopressin use for adult enuresis increased with age. Orally disintegrating tablets were the most frequently used formulation (57%–65% of prescriptions), and a greater proportion of women than men used low‐dose desmopressin (60 μg). Concomitant use of painkillers (opioids: 18%–26.7% of prescriptions; non‐steroidal anti‐inflammatory drugs: 14.2%–16.4% of prescriptions) and antidepressants (14.4%–18.1% of prescriptions) was common in both conditions, and 5.4%–9.2% of concomitant prescriptions were for overactive bladder medications. Conclusions: This study provides insights into desmopressin use among Danish adults. Nearly half the prescriptions were to patients aged ≥65 years, despite historical manufacturer recommendations that desmopressin be restricted to patients <65 years of age. NE is considered a childhood condition, but desmopressin use for adult NE increased with age. A greater proportion of desmopressin prescriptions to women than men were for the lowest dose, consistent with greater sensitivity to desmopressin in women.